2022
DOI: 10.1212/wnl.0000000000200349
|View full text |Cite|
|
Sign up to set email alerts
|

Impulsivity Trait Profiles in Patients With Cerebellar Ataxia and Parkinson Disease

Abstract: Background and Objectives:Individuals with cerebellar ataxia (CA) can develop impulsive behavioral symptoms, often resulting in negative interpersonal consequences, detrimentally impacting their quality of life. Limited evidence exists concerning impulsivity in CA and its associated behavioral changes. We assessed impulsive traits in CA using the Barratt impulsivity scale (BIS-11) and compared them with those of Parkinson disease (PD), in order to investigate the differences in the impulsive trait profiles bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…52,53 In particular, recent findings have indicated that individuals with CA have heightened domain-specific impulsive and compulsive behaviors, which is a common symptom of underlying reward system dysfunction. 54,55 Our study adds to this work by suggesting that the cerebellum is additionally necessary for reward learning in humans.…”
Section: Discussionmentioning
confidence: 60%
“…52,53 In particular, recent findings have indicated that individuals with CA have heightened domain-specific impulsive and compulsive behaviors, which is a common symptom of underlying reward system dysfunction. 54,55 Our study adds to this work by suggesting that the cerebellum is additionally necessary for reward learning in humans.…”
Section: Discussionmentioning
confidence: 60%
“…This is consistent with the recently reported findings of distinctive impulsive patterns between Parkinson's disease and cerebellar ataxia. 26 The traditional reward mesolimbic pathway connects the VTA to ventral striatum. 19 , 41 Recent animal studies have exhibited the important role of the cerebellum in different stages of reward processing.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 , 12 , 13 Consistently, we found patients with cerebellar ataxia have increased ICBs, supporting the notion of abnormal reward processing. 24 Given that the impulsivity and compulsivity could greatly impact the quality of life for people living with ataxia and their families, 23 such as the non‐planning impulsive traits (e.g., spending money without thinking about the consequences) identified in cerebellar ataxia, 26 a validated scale to allow further probing the mechanism of ICBs in cerebellar disorders is necessary. CIA can be used at bedside and office as a time and cost‐effective screening tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Research Article “Impulsivity Trait Profiles in Patients With Cerebellar Ataxia and Parkinson Disease” by Chen et al, 1 Figure 2A should be labeled “First-order factors: CA vs control.” The editorial staff regret the error.…”
mentioning
confidence: 99%